PENERAPAN PEMBELAJARAN AQIDAH AKHLAK DALAM MEMBENTUK PERILAKU TERPUJI SISWA KELAS III MADRASAH IBTIDAIYAH TEMPURSARI SAMBI BOYOLALI TAHUN AJARAN 2022/2023 - Rahma, Salma Nur; Mujiburrahman, M; Nurhidayati, Indah (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2023)
The purpose of this study is to determine the application of Aqidah Akhlak learning in general in grade 3 at Madrasah Ibtidaiyah (MI) Tempursari, to determine the application of Aqidah learning to the behavior of grade 3 students at Madrasah Ibtidaiyah (MI) Tempursari, and at the same time to find out the various moral problems of grade 3 students in Madrasah Ibtidaiyah (MI) Tempursari. This type of research is qualitative field research. The subjects in this study were third grade students, totaling 32 students and aqidah akhlak subject teachers of Madrasah Ibtidaiyah Tempursari Sambi Boyolali. The informants in this study were the head of the madrasah and the third grade teacher at MI Tempursari. Some of the methods that the author uses in data collection are observation, interviews, and documentation. The results of this study indicate that there is an impact of exemplary for third grade students of MI Tempursari, that with the exemplary of educators or teachers through learning aqidah akhlak, students can form their praiseworthy behavior. With increasing daily values and a better personality. With the teacher giving examples of adab eating and drinking using the right hand and sitting, so that students follow the same thing because the teacher gives an example.